The use of the terrestrial snails of the genera Megalobulimus and Thaumastus as representatives of the atmospheric carbon reservoir - Macario, K; Alves, E; Carvalho, C; Oliveira, F; Ramsey, C; Chivall, D; Souza, R; Simone, L; Cavallari, D (Nature Publishing Group, 2016)
In Brazilian archaeological shellmounds, many species of land snails are found abundantly distributed throughout the occupational layers, forming a contextualized set of samples within the sites and offering a potential alternative to the use of charcoal for radiocarbon dating analyses. In order to confirm the effectiveness of this alternative, one needs to prove that the mollusk shells reflect the atmospheric carbon isotopic concentration in the same way charcoal does. In this study, 18 terrestrial mollusk shells with known collection dates from 1948 to 2004 AD, around the nuclear bombs period, were radiocarbon dated. The obtained dates fit the SH1-2 bomb curve within less than 15 years range, showing that certain species from the Thaumastus and Megalobulimus genera are reliable representatives of the atmospheric carbon isotopic ratio and can, therefore, be used to date archaeological sites in South America.